Dietary ambon lumut banana stem extract Musa cavendishii var. dwarf Paxton as an immunostimulant for white spot disease prevention in Pacific white shrimp Litopenaeus vannamei - Ramadhan, Afriani; Nuryati, Sri; Priyoutomo, Nur Bambang; Alimuddin, Alimuddin (Jurnal Akuakultur Indonesia, 2017)
ABSTRACT This study was aimed to evaluate the dietary ambon lumut banana Musa cavendishii var. dwarf Paxton stem extract on the immune responses, growth, and survival rate of Pacific white shrimp against white spot disease. Ambon banana steam extract was obtained by maceration method using ethanol. The shrimps fed by pellet containing ambon banana stem extracts with different dosages for 29 days, i.e designated as 0.1 (A); 0.3 (B), and 0.5 (C) g/kg, the diet treatment without ambon banana stem extract without challenged test (K-), and diet treatment without ambon banana stem extract with challenged test (K+). Each treatment consisted of three replications. Feeding was conducted for 29 days of maintenance (four times a day). The results showed that the immune responses (average total hemocyte count: 45.15×106 cells/mL, phenoloxidase activity 1.03±0.08 OD, respiratory burst 0.95±0.04 OD, phagocytic activity 94.33±1.53%, growth (specific growth rate: 7.79±0.06%/day, feed ratio conversion was 52±0.01), and survival of treatment C (survival rate 100%) were higher compared with the treatment K+ (total hemocyte count: 3.83×106 cells/mL, phenoloxidase activity 0.04±0.01 OD, respiratory burst 0.18±0.06 OD,  phagocytic activity 5.67±0.58%, specific growth rate: 2.61±0.08%/day, feed conversion ratio 2.11±0.02, survival rate: 50%). Therefore, banana stem extract at a dose of 0.5 g/kg everyday diet can be used to improve growth and nonspecific immune system against white spot disease on Pacific white shrimp. Keywords: Pacific white shrimp, white spot disease, immune response, Ambon banana stem extract  ABSTRAK Penelitian ini bertujuan untuk menguji dosis optimal ekstrak batang pisang ambon melalui pakan dalam meningkatkan respon imun, pertumbuhan dan kelangsungan hidup udang putih terhadap penyakit white spot. Ekstrak batang pisang ambon lumut Musa cavendishii var. dwarf  Paxton menggunakan metode maserasi dengan menggunakan pelarut etanol. Pakan udang yang mengandung ekstrak batang pisang ambon pada dosis yang berbeda selama 29 hari 0,1 (A); 0,3 (B), dan 0,5 (C) g/kg, pakan tanpa pemberian ekstrak batang pisang ambon dan tidak diuji tantang (K-), pakan tanpa pemberian ekstrak batang pisang ambon dan diuji tantang (K+). Masing-masing perlakuan terdiri atas tiga ulangan. Frekuensi pemberian pakan empat kali sehari selama 29 hari pemeliharaan. Hasil penelitian menunjukkan bahwa perlakuan C respons imun (rata-rata jumlah total hemosit: 45,15×106 sel/mL, aktivitas phenoloxydase 1,03±0,08 OD, respiratory burst 0,95±0,04 OD, aktivitas fagositik 94,33±1,53%, pertumbuhan (laju pertumbuhan spesifik: 7,79±0,06%/hari, rasio konversi  pakan 0,52±0,01), dan kelangsungan hidup  (survival rate 100%) lebih tinggi dibandingkan dengan perlakuan K+ (jumlah total hemosit: 3.83×106 sel/mL, aktivitas phenoloxydase 0,04±0,01 OD, respiratory burst 0,18±0,06 OD, aktivitas fagositik 5,67± 0,58%, laju pertumbuhan spesifik: 2,61±0,08%/hari, rasio konversi pakan 2,11±0,02, nilai kelangsungan hidup: 50%). Jadi, ekstrak batang pisang pada dosis 0,5 g/kg setiap hari pada pakan dapat digunakan untuk meningkatkan pertumbuhan dan sistem kekebalan tubuh nonspesifik terhadap penyakit bintik putih pada udang putih.   Kata kunci: udang putih, white spot, respons imun, ekstrak batang pisang ambon